2013
DOI: 10.1246/cl.130143
|View full text |Cite
|
Sign up to set email alerts
|

Successive Formation of Two Amide Linkages between Two Benzene Rings

Abstract: To successively construct two amide bonds between two benzene rings, the reaction of methyl N-alkylanthranilate and N-alkylisatoic anhydride in the presence of a base was studied. When the reaction was carried out with lithium hexamethyldisilazide and N,N,N′,N′-tetramethylethylenediamine in THF at 70 °C under reduced pressure, a cyclic diamide was obtained in high yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…9 The reaction tube was sealed after the pressure inside the tube had been reduced, and the reaction mixture was heated at 70°C for 1 h. SEC analysis of the reaction mixture revealed that the reaction almost ceased in 5 min despite incomplete consumption of the monomers, and an oligomeric product (M n = 2040, M w = 3020) was formed ( Figure 1a). As shown in Figure 2a, the MALDI-TOF mass spectrum of the crude product showed molecular ion peaks whose m/z values agreed with the molecular weight of the linear-type products, such as A − (BA) n − A type oligomers 9 (n = 1-3) and an amideterminated oligomer 10 ( Figure 3).…”
Section: Polymerization Of a 2 -And B 2 -Type Monomersmentioning
confidence: 99%
See 2 more Smart Citations
“…9 The reaction tube was sealed after the pressure inside the tube had been reduced, and the reaction mixture was heated at 70°C for 1 h. SEC analysis of the reaction mixture revealed that the reaction almost ceased in 5 min despite incomplete consumption of the monomers, and an oligomeric product (M n = 2040, M w = 3020) was formed ( Figure 1a). As shown in Figure 2a, the MALDI-TOF mass spectrum of the crude product showed molecular ion peaks whose m/z values agreed with the molecular weight of the linear-type products, such as A − (BA) n − A type oligomers 9 (n = 1-3) and an amideterminated oligomer 10 ( Figure 3).…”
Section: Polymerization Of a 2 -And B 2 -Type Monomersmentioning
confidence: 99%
“…In these polymerizations, the deprotonated amide ion of the monomer attacks the carbonyl group adjacent to the benzene ring at the isatoic anhydride moiety of another monomer, leading to the formation of an amide linkage and a carbamate ion. 9 If decarbonation of the carbamate ion occurs and the formed amide ion attacks the neighboring ester moiety, the ladder structure will be obtained. We believe that the electron-withdrawing carbonyl group at the para position of the nitrogen atom of 2 and 4 reduces the nucleophilicity of the amide ion formed by the decarbonation, retarding the formation of the ladder structure.…”
Section: Polymerization Of Diaminoisophthalate Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Aiming to synthesize ladder‐type aromatic polyamides, we studied the reaction between N ‐methylanthranilic acid methyl ester ( 1 ) and N ‐methylisatoic anhydride ( 2 ) in the presence of a strong base as a model reaction and observed that the use of lithium hexamethyldisilazide (LiHMDS) as a base resulted in exclusive formation of two amide linkages successively between the two benzene rings to afford 3 (Scheme ) . For the synthesis of ladder polymers using this reaction, the polymerization of 4,6‐diaminoisophthalic acid monomers 4 bearing an anthranilic acid ester moiety and an isatoic anhydride moiety was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…As in the case of the reaction we reported previously, 8 the dimer methyl ester was synthesized by the reaction of methyl N-isopropylanthranilate with N-isopropylisatoic anhydride in…”
mentioning
confidence: 99%